Perilaku Konsumen terhadap Pembelian Minuman Kopi Goncang Lidah Coffee Shop Sungai Pinyuh Kabupaten Mempawah - Zaiyus Triona Yona; Janne Hillary (Vokasi: Jurnal Publikasi Ilmiah, 2025)
The aim of this research is to find out partially or simultaneously whether there is an influence of cultural factors, social factors, personal factors and psychological factors on the decision to purchase Goncang Lidah coffee drinks. The sample in this research was 54 consumers. This research analysis uses the Multiple Linear Regression analysis method, the results of data analysis using SPSS 23. Quantitative method is a type of research that is based on the philosophy of positivism and is used to research certain populations or samples, data collection techniques use research instruments, data analysis is quantitative/statistical with the aim of testing predetermined hypotheses. This research was carried out including a Likert scale, validity test, reliability test, classical assumption test which includes the normality test, multicollinearity test and heteroscedasticity test, multiple linear regression, hypothesis testing which includes the determination test (R2), F test and t test. From the results of the t test, personal factors have a significant influence on purchasing Goncang Lidah Sungai Pinyuh coffee drinks, Mempawah Regency.